Reading theories and telling stories in contemporary fiction - McNally, L (2012)
My thesis engages with reader-response theory in order to show how the realisations it makes might be refined by deconstruction. Reader-response theorists such as Stanley Fish and Norman Holland acknowledge that a subjective element inheres within all interpretation. This has an unsettling effect for literary criticism, which traditionally grounds its claims on notions of objectivity. Criticism must be rethought; both Fish and Holland promise to practise a self-conscious literary criticism which represents more accurately the experience of reading. My thesis begins with an analysis of reader-response which demonstrates, however, that its attempt to inscribe the act of reading fails; it takes place within a text which is read. Reading inevitably recedes. Neither Fish nor Holland explicitly addresses this dilemma. Deconstruction, on the other hand, takes it into account; it works with, not in spite of, it in order to show that self-consciousness must be approached in a certain way if it is to remain useful. My thesis does not therefore offer a new theory of reader-response but rethinks this phase within the history of theory by responding to the challenge presented by a recent self-consciousness in theory and literature alike. I show that it is possible, in reading works of contemporary fiction alongside texts by Derrida (and those who think after him), to deepen our understanding of what it is to read. Reading cannot be grasped; it is marked by that which cannot be known. Its drama resounds with the recent shift towards a notion of ethics predicated upon the unknowability of the other. My thesis wonders repeatedly what consequences this appearance of the unknowable has for literary criticism; to acknowledge its centrality is to accept that the role of criticism cannot be to fully capture the text. Instead, the readings I offer remain attentive, in the face of their failure, to the irrecoverable.